(untitled) (Journal of Medicine, 2008)
The Descriptive cross sectional study was conducted over the period of 1st July 2006 to 30th June 2007 (one year) to estimate disability burden and economic loss incurred by cancer patients. The study was carried out among 224 cancer patients who attended the National Institute Cancer Research & Hospital (NIRCH). Data was collected by face-to-face interview using a semi-structured questionnaire and systematic random sampling technique. Disability burden of cancer was measured in terms of years of life lived (YLD) and economic loss was estimated by health care expenditure incurred by the cancer patients. Out of all, major part (59.82%) was male while 40.18% was female and most of them were in middle age group (40-49 years) with mean age of 49.18 (SDÂ±14.66) years. Most of the patients (93%) were Muslims and majority (83%) was married. Maximum number of patients (38.39%) had primary level education with a large illiterate segment (27.68%). By occupation, maximum patients were housewives (28.73%) followed by agriculturers (25.50%). The average family size was 4.6 (SDÂ±2.53) and majority (39.28%) was in poor income group ( < Tk.5000). According to primary site, common cancers included cancer of lung (25%) & cervix (16.96%) followed by cancer of breast (13.39%), lymph node & lymphatic (6.70%), larynx (5.36%), oral cavity (5.36%), oesophagus (4.46%), leukemia (4.46%), bone & cartilage (4.02%), stomach (2.68%), skin (2.68%), prostate (1.79%), liver (0.89%), endocrine gland (0.89%) & caner of unknown primary origin (5.36%). Most male cancer patients (73.88%) had smoking habit in contrast to 7.78% female patients, which showed statistical significance (Ï2 test, p < 0.01). Male patients shared more YLDs (64%) than female patients (36%), which was statistically significant (ât’ test, p < 0.05). It was emerged that the highest YLD was shared by the active age group (63.8%), middle-income group (40.35%) and by poorly educated patients (69%). Average treatment cost incurred by the cancer patients was TK.5,773.11 (Â±SD272.39) and it was more among the higher income, middle age and educated patients, which were statistically significant (ANOVA, p < 0.01). Male patients shared higher average treatment cost (TK.7,158.65 Â±SD337.76) than their female counterparts (TK.4387.57 Â±SD 207.02) and revealed statistical significance (ât’ test, p < 0.01). Ca Lung incurred highest average treatment cost (TK.8,247.86 Â±SD121.43) followed by Ca cervix (TK.7,787.73 Â±SD118.56) and Ca breast (TK.7,183.53 Â±SD104.63). Half of the patients were treated by combination of surgery, chemotherapy & radiotherapy and surgery being most costly (TK.8,574.96 Â±SD 455.23), which was statistically significant (ANOVA, p < 0.01). Key Words: Cancer, Disability burden, YLD, Economic Loss. Â DOI = 10.3329/jom.v9i1.1418 J MEDICINE 2008; 9 : 3-9